2021
DOI: 10.1111/iji.12529
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HLA‐DQA1, ‐DQB1 and ‐DRB1 genes and haplotypes in Han, Uyghur, Kazakh and Hui populations inhabiting Xinjiang Uyghur Autonomous Region, China

Abstract: Genetic polymorphisms of human leucocyte antigen (HLA)-DRB1, -DQA1 and -DQB1 among four main ethnic groups including Han (n = 70), Uyghur (n = 71), Kazakh (n = 52) and Hui (n = 40) subjects from Xinjiang Uyghur Autonomous Region were investigated using a polymerase chain reaction-sequence-based typing (PCR-SBT). In total, 32 HLA-DRB1 alleles, eight HLA-DQA1 alleles and 14 HLA-DQB1 alleles were identified. The most predominant HLA-DRB1, -DQA1 and -DQB1 alleles were DRB1*15:01 (12.50%), DQA1*01:02 (21.43%) and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Compared to the previous study, 31 HLA‐DQA1 alleles showed a concordance rate of 78.9% (15/19) (Table S1 (summarized in Table 1 (allele frequency > 1.5%, concordance rate of 100%))). In addition to the IMGT/HLA database, investigations were recently conducted on exon 2 of HLA‐DQA1 48,49 . This can be overcome by targeting exons 2 and 3, as done in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the previous study, 31 HLA‐DQA1 alleles showed a concordance rate of 78.9% (15/19) (Table S1 (summarized in Table 1 (allele frequency > 1.5%, concordance rate of 100%))). In addition to the IMGT/HLA database, investigations were recently conducted on exon 2 of HLA‐DQA1 48,49 . This can be overcome by targeting exons 2 and 3, as done in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the database, investigations were recently conducted on exon 2 of HLA-DQA1. 48,49 This can be overcome by targeting exons 2 and 3, as done in this study. HLA-DQA1 genotype identified by NGS has been reported as a single allele or a group of alleles with polymorphisms outside exons 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 87.3% of the patients were of Uygur and Kazakh ethnicities. The phylogenetic dendrogram constructed in 13 populations in Asia, Central Asia, and Europe according to the allele frequencies of HLA‐DRB1, ‐DQA1, and ‐DQB1 showed that the Kazakh and Uygur ethnic groups have similar genetic backgrounds 46 …”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic dendrogram constructed in 13 populations in Asia, Central Asia, and Europe according to the allele frequencies of HLA-DRB1, -DQA1, and -DQB1 showed that the Kazakh and Uygur ethnic groups have similar genetic backgrounds. 46 There were some limitations to the current study. The small sample size might have reduced the statistical power of the study and limited our analysis.…”
Section: Hla-dq Distributionmentioning
confidence: 91%